(untitled) (Research, Society and Development, 2022)
Research on the wave-particle behavior of light gave rise to Quantum Physics, based on the idea of ​​quantization of energy, suggested by Max Planck. In this sense, it is important that students understand that light has wave behavior when propagating and corpuscular behavior when interacting with matter. This work aims to report the potential of a didactic proposal for teaching the dual nature of light. Therefore, the proposal under analysis was based on the theory of Meaningful Learning, also promoting an appreciation of the History of Science in Physics classes, as a methodological tool. And yet, it brings two experiments to promote a better understanding of the duality of light. The research is characterized as qualitative, the data were collected during all its actions, consisting of questionnaires, transcribed speeches, conceptual maps and a field diary. It was found that the students had a good receptivity to the proposed activities, presenting at the end, important relationships about the duality of light, referring to a new meaning of concepts from their previous knowledge, obtaining new scientific knowledge with the social aspects as advocate the Curriculum Guidelines for Basic Education in the state of Paraná.